Optimizing the Protein Fluorescence Reporting System for Somatic Embryogenesis Regeneration Screening and Visual Labeling of Functional Genes in Cotton - Hu, Gai-Yuan; Ma, Jia-Yi; Li, Fen; Zhao, Jing-Ruo; Xu, Fu-Chun; Yang, Wen-Wen; Yuan, Man; Gao, Wei; Long, Lu (Frontiers in Plant Science, 2022)
Protein fluorescence reporting systems are of crucial importance to in-depth life science research, providing systematic labeling tools for visualization of microscopic biological activities in vivo and revolutionizing basic research. Cotton somatic cell regeneration efficiency is low, causing difficulty in cotton transformation. It is conducive to screening transgenic somatic embryo using the fluorescence reporting system. However, available fluorescence labeling systems in cotton are currently limited. To optimize the fluorescence reporting system of cotton with an expanded range of available fluorescent proteins, we selected 11 fluorescent proteins covering red, green, yellow, and cyan fluorescence colors and expressed them in cotton. Besides mRuby2 and G3GFP, the other nine fluorescent proteins (mCherry, tdTomato, sfGFP, Clover, EYFP, YPet, mVenus, mCerulean, and ECFP) were stably and intensely expressed in transgenic callus and embryo, and inherited in different cotton organs derive from the screened embryo. In addition, transgenic cotton expressing tdTomato appears pink under white light, not only for callus and embryo tissues but also various organs of mature plants, providing a visual marker in the cotton genetic transformation process, accelerating the evaluation of transgenic events. Further, we constructed transgenic cotton expressing mCherry-labeled organelle markers in vivo that cover seven specific subcellular compartments: plasma membrane, endoplasmic reticulum, tonoplast, mitochondrion, plastid, Golgi apparatus, and peroxisome. We also provide a simple and highly efficient strategy to quickly determine the subcellular localization of uncharacterized proteins in cotton cells using organelle markers. Lastly, we built the first cotton stomatal fluorescence reporting system using stomata-specific expression promoters (ProKST1, ProGbSLSP, and ProGC1) to drive Clover expression. The optimized fluorescence labeling system for transgenic somatic embryo screening and functional gene labeling in this study offers the potential to accelerating somatic cell regeneration efficiency and the in vivo monitoring of diverse cellular processes in cotton.